Effect of Water Hyacinth’s Particle Size as Additional Substrate to the Leachate Anaerobic Bioreactor - Ramadhani, Laily Isna; Widyabudiningsih, Dewi; Wirawan, Feri; Almarnugraha, Aditya; Setyaningrum, Sinta (Fluida, 2024)
Municipal solid waste leachate contains landfill-produced organic contaminants. Leachate with the high organic content pottentially pollute nearby waterways. The high content of pollutants in leachate is represented by the measured Chemical Oxygen Demand (COD) content. Therefore, leachate was carried out using the anaerobic method. The anaerobic approach was chosen because it can process high-organic waste and produce biogas, in which methane in biogas may be used as renewable energy. Leachate from old landfills is heavy in nitrogen, thus to optimize the anaerobic process, it must be mixed with high-carbon substrates. Water hyacinth, a fast-growing plant with a high carbon content, is a weed because it pottentially damage the ecosystem. This research begins by comparing the anaerobic reactor with a single substrate of leachate and a mixed substrate (leachate and water hyacinth). Water hyacinth was added with size variations of 1 mm; 5 mm; 10 mm; and 15 mm. From the four variations, the mixed substrate reactor had a higher COD reduction efficiency than the single substrate in all water hyacinth sizes. The optimum particle size of water hyacinth is 1 mm, resulted the highest COD reduction efficiency of 81% and the highest biogas cummulative volume of 4,230 mL. The addition of water hyacinth as an additional substrate statisticaly proven has a strong correlation to the increasing efficiency of COD removal compared to the biogas production.